The role of BioBlitzes in citizen science: insights from participants and experts - Tiago, P.; Evaristo, I.; Pinto, B. (Frontiers in Environmental Science, 2024)
Beyond its primary role in generating scientific knowledge, citizen science also carries a potent educational dimension. An example of citizen science activities is BioBlitzes, which are collaborative events that bring together both experts and citizens, all united by a common mission: to register species observations within a defined geographical area during a predetermined time frame. In addition to comprehensively characterizing BioBlitz participants across sociodemographic, emotional, and cognitive domains, this study seeks to gain insights into the overall perceptions held by BioBlitz experts regarding these events and their participants. By considering both perspectives, we strive to achieve a more holistic understanding of BioBlitzes, elucidating their significance and impact on both the individuals participating and the broader scientific community involved. The analyzed sample corresponded to 96 participants and 11 experts. The evaluation made by the 96 participants was carried out by applying a pre-questionnaire and post-questionnaire, which allowed us to conclude that the participants, in the short term, acquired some knowledge during the event, but few emotional changes were detected. The evaluation made by the 11 experts was carried out in two online focus group sessions. It was concluded that there is a general opinion that citizens and experts learn during a BioBlitz and appreciate the social dimension of these experiences and that citizens leave the BioBlitz with more awareness of nature conservation issues.